Structural Foundation Planning of the Faculty of Economics Building at the University of Bojonegoro - Bella Lutfiani Al Zakina; Sujiat Sujiat; Toni Budi Santoso; Uki Firmanto; M Zainul Ikhwan; Zainnudin Zainnudin; R. Muhammad Ernadi Ramadhan (Electronic Journal of Education, Social Economics and Technology, 2025)
The building in general has two parts, namely the upper structure and the lower structure. The upper structure consists of the floor, walls, and roof of the building, while the lower structure consists of the foundation and sloof. The construction of this building aims as an effort to develop and add teaching and learning spaces and office space for the Faculty of Economics at Bojonegoro University. In this planning using the guidelines of SNI 1727-2020 (BeSNI 1727-2020 (Minimum design loads and related criteria for buildings and other structures), SNI 1726-2019 (Earthquake Resistant building procedures), SNI-2847-2019 (Structural concrete requirements for buildings) and SNI 1729-2020 (Specifications for structural steel buildings). Based on the results of the planning of the University of Bojonegoro Economic Building using Sloof 35 x 55 cm with pilecap foundation 150 x 150 cm and bored pile depth of 500 cm.